Discriminating Value of Calprotectin in Disease Activity and Progression of Nonradiographic Axial Spondyloarthritis and Ankylosing Spondylitis. (15th May 2017) - Huang, Jinxian; Yin, Zhihua; Song, Guoxiang; Cui, Shengjin; Jiang, Jinzhao; Zhang, Lijun
Abstract : It has been controversial whether ankylosing spondylitis (AS) and nonradiographic axial spondyloarthritis (nr-axSpA) are separate or different phases of radiographic progression. We determined that serum calprotectin level (ng/ml) was higher in AS (15.30 ± 6.49) and nr-axSpA (17.76 ± 8.59) patients than in healthy individuals (7.40 ± 2.67). No difference was observed in calprotectin level between these two groups. Elevated calprotectin was positively correlated with ESR, CRP, BASDAI, and ASDAS as well as SPARCC scoring and had no correlation with BASFI and mSASSS. No correlation was observed between calprotectin and Wnt/ β -catenin pathway markers. Serum calprotectin can be used as a marker for inflammation in both nr-axSpA and AS, while it does not contribute to the discrimination of AS and nr-axSpA. Calprotectin-mediated inflammation was not correlated with principle effectors of Wnt/ β -catenin pathway, indicating that inflammation and bone fusion might be separate processes of the disease.